Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/path.5000
|View full text |Cite
|
Sign up to set email alerts
|

Decoy receptor 3 promotes cell adhesion and enhances endometriosis development

Abstract: Endometriosis is a multifactorial inflammatory disease with persistent activation of the nuclear factor-κB (NF-κB) signalling pathway. Aberrant adhesion of endometrium is the essential step in the progression of endometriosis, but the molecular mechanism of ectopic growth of endometrium is still unclear. Decoy receptor 3 (DcR3)/TNFRSF6B, a pleiotropic immunomodulator regulated by oestrogen, is able to activate focal adhesion kinase to promote cell adhesion. We found that DcR3 is upregulated in human ectopic en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 55 publications
(81 reference statements)
1
14
0
1
Order By: Relevance
“…For instance, decoy receptor 3 ( DcR3 )/ TNFRSF6B , a pleiotropic immunomodulator regulated by estrogen, promotes cell adhesion and enhances endometriosis development by activating focal adhesion kinase (FAK). [ 29 ] PGC-1α , highly expressed in ovarian endometrioma, promotes local estrogen biosynthesis by stimulating aromatase expression and activity. [ 30 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, decoy receptor 3 ( DcR3 )/ TNFRSF6B , a pleiotropic immunomodulator regulated by estrogen, promotes cell adhesion and enhances endometriosis development by activating focal adhesion kinase (FAK). [ 29 ] PGC-1α , highly expressed in ovarian endometrioma, promotes local estrogen biosynthesis by stimulating aromatase expression and activity. [ 30 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 38 ] Moreover, the evidence revealed that TNFRSF6B stimulated endometriosis development by activating FAK. [ 29 ]…”
Section: Discussionmentioning
confidence: 99%
“…In term of risk of EOC/TC, there are a lot factors relating to the risk of EOC/TC, including genetic background, parity, the use of oral pills, hysterectomy, endometriosis, and PID. [ 44 49 ] The diagnosis of EOC/TC is often difficult and always delayed, contributing to more than two-thirds of cases of EOC/TC diagnosed when the disease has progressed to stage III or IV and involves the peritoneal cavity or other organs. [ 50 52 ] To overcome the above-mentioned limitation, many researchers attempted to make an early diagnosis of EOC/TC and decrease the EOC/TC-related morbidity or mortality using the different kinds of strategies [ 53 57 ] ; however, results are relatively disappointing.…”
Section: Discussionmentioning
confidence: 99%
“…The role of NF-kB mediation of cellular adhesion processes is also of interest in the context of cancer immunotherapy [ 139 ], although the mechanism by which pathological NF-kB activation occurs in malignant disease remains a subject of ongoing debate. The role of decoy receptor 3 (DcR3) has been proposed as a potential mechanism to promote cell adhesion in the development of endometriosis [ 140 ]. DcR3 has long been recognised as a method by which cancer cells may evade NK and cytotoxic T-cells via the inhibition of FasL-induced apoptosis [ 141 ].…”
Section: Malignancymentioning
confidence: 99%
“…DcR3 has long been recognised as a method by which cancer cells may evade NK and cytotoxic T-cells via the inhibition of FasL-induced apoptosis [ 141 ]. Tsai et al [ 140 ] noted an increased activation of the Akt-NF-kB signalling pathway in ectopic endometrium, with consequent upregulation of DcR3. In this xenograft study, DcR3 expression levels correlated both with ICAM-1 levels and with those of homing cell adhesion molecule (HCAM).…”
Section: Malignancymentioning
confidence: 99%